Determination of chlorophenols in honey samples using in-situ ionic liquid-dispersive liquid–liquid microextraction as a pretreatment method followed by high-performance liquid chromatography. (1st May 2015) - Fan, Chen; Li, Nai; Cao, Xueli
Highlights: In-situ IL-DLLME method was developed for the detection of CPs in honey samples. A back-extraction method was proposed to eliminate the interference of ILs. Several factors affecting extraction efficiency were optimised systematically. The method is rapid and efficient with high recovery and high reproducibility. Abstract: In-situ ionic liquid-dispersive liquid–liquid microextraction (IL-DLLME) method was developed as a pretreatment method for the detection of six chlorophenols (CPs) in honey samples. The hydrophobic ionic liquid [C4 MIM][NTf2 ], formed in-situ by the hydrophilic ionic liquid [C4 MIM][BF4 ] and the ion exchange reagent LiNTf2 was used as the microextractant solvent of CPs from honey sample. Then the enriched analytes were back-extracted into 40 μL of 0.14 M NaOH solution and finally subjected to analysis by high-performance liquid chromatography. The method showed low limit of detection of CPs, 0.8–3.2 μg/L and high enrichment factor, 34–65 with the recoveries range from 91.60% to 114.33%. The method is simple, rapid, environmentally friendly and with high extraction efficiency.